Thermal characteristics of a seasonal solar assisted heat pump heating system with an underground tank. (February 2020) - Huang, Haotian; Xiao, Yimin; Lin, Jianquan; Zhou, Tiecheng; Liu, Yanan; Zhao, Qian
Highlights: Propose a 2D model for seasonal thermal storage system with an underground tank. The model considers the stratification in tanks and the outside temperature field. Discuss the dynamic charge and discharge characteristics of SSTES. Discuss the effect of the tank's thermal insulation level on the system operation. Abstract: Seasonal solar thermal energy storage could be an effective way to relieve energy problems. However, the large storage volume such systems require restricts their practical application. To overcome this problem, this paper proposes a method that increases the heat storage capacity of an underground water tank by coupling it with the soil for heating. In order to consider the stratification of water in a long-term simulation, a two-dimensional computational model was established based on the plug flow model and the finite difference method to simulate the instantaneous temperature field. Further, the accuracy of the model was verified via a model experiment. The dynamic charge and discharge characteristics were numerically studied, and the effect of the tank's thermal insulation level was discussed. We simulated the hourly load of a building throughout a year, and the operation of the heat storage system throughout 10 years based on local hourly meteorological data. The results show that the heat storage capacity of the system can be effectively improved by insulating only the upper half of the tank.